Phonological Interference of Japanese Uvular [ɴ] in the pronunciation of English Alveolar /n/ at Ending Distribution - Anisah Durrotul Fajri (Universitas Sebelas Maret, 2025)
English has been widely used all around the world, either as the first, second, or foreign languages. As foreign language of Japan, English is not daily used, however, since immigration to English speaking countries for educational or business purposes has been common in Japan, more and more people used English within those contexts. A case on the use of English by Japanese is a vlogger Rion Ishida whose speech frequently used uvular [ɴ] for English alveolar /n/. This study examined the interference of Japanese uvular [ɴ] which is not common in English in the speech production of English alveolar /n/. The finding shows that at ending distribution, English alveolar /n/ has been pronounced as uvular [ɴ] in more-than-one-syllable words. In this case, actual phoneme substitution occurs as a result of phonological interference. This is partly caused by the position of the words containing /n/ in the speech and another is caused by the interference of Japanese phonological system which regulates alveolar /n/ to be realized as uvular [ɴ] at final or ending distribution. Thus, three factors causing phonological interferences consisting (1) the competing phonemic categories, (2) their allophonic membership, and (3) their distributions are all evident in this study.